Knowlegde, Attitude and Practice of Vaginal Douching in Non-Medical Undergraduates in a South Eastern Nigerian University - UWAKWE, Emmanuel Chijioke; IKOBHO, Ebenezer Howells; DARLINTON-PETER CHIBUZOR, UGOJI; Idika, Idika Mba; ONWE, Cletus Uchechukwu; ORTUANYA, Kelvin Emeka; MARCEL-ONWUDIWE, Chinomnso Stella (International Journal of Innovative Research in Medical Science, 2024)
Background: Vaginal douching is the process of intravaginal cleansing with a liquid solution. It is a harmful practice performed by millions of women all over the world with little knowledge about its harmful effect on their reproductive and overall health. Vaginal douching changes the microflora of the vagina thereby predisposing the individual to vaginal infections and its complications. Aim: This study was aimed to determine the knowledge attitude and practice of vaginal douching in non-medical undergraduates of Ebonyi State University Abakaliki. Methodology: This was a cross-sectional study using self-administered questionnaire. The sociodemographic factors of the respondents alongside their knowledge, attitude and practice of vaginal douching were assessed. The results were analyzed using the Epi info version 7. The level of significance was set at p<0. 05. Results: The prevalence of vaginal douching obtained was 52%. Forty-eight percent of them were introduced to vaginal douching by their mother. 66. 4% of them were sexually active. Forty-seven respondents (54. 2%) of them have been involved in vaginal douching. One hundred and thirty-three respondents (49. 1%) have had vaginal symptoms in the past. The presence of vaginal symptoms occurred in 71% of the respondents that are douching. While these vaginal symptoms occurred in 29% of the respondents that are not douching. Conclusion: The study showed high prevalence practice of vaginal douching with its attendance sequale. Therefore, Health enlighten programs should be advocated and laws prohibiting the sale of douching products should be instituted.